Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/ped.14890
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 in healthy children: What is the effect of household contact?

Abstract: Background Coronavirus disease 2019 (COVID‐19) in children is milder than in adults. Household virus exposure may affect clinical severity. We aimed to determine the household contact history of patients and its influence on the clinical stage. Methods One hundred and seventy‐three pediatric patients with COVID‐19 as diagnosed with positive real‐time polymerase chain reaction for severe acute respiratory syndrome coronavirus‐2 aged 1 month to 18 years were included. Demographic data, laboratory and clinical fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
6
2
Order By: Relevance
“…However, we would like to re-emphasize that examining the spread of SARS-CoV-2 from child to adult or vice versa was not an aim of our study. Soyemi et al reference a study (Ustundag et al) [7] in their letter that displayed different findings than our study. Ustundag et al examined if contact with a household family member with SARS-CoV-2 was associated with clinical outcomes (e.g., hospitalization) in patients aged one month to 18 years with SARS-CoV-2.…”
contrasting
confidence: 89%
“…However, we would like to re-emphasize that examining the spread of SARS-CoV-2 from child to adult or vice versa was not an aim of our study. Soyemi et al reference a study (Ustundag et al) [7] in their letter that displayed different findings than our study. Ustundag et al examined if contact with a household family member with SARS-CoV-2 was associated with clinical outcomes (e.g., hospitalization) in patients aged one month to 18 years with SARS-CoV-2.…”
contrasting
confidence: 89%
“…Among 10 studies reporting the hospitalization status of cases (Fig. 5A), 8 studies reported higher proportion of hospitalization for index cases than secondary cases 30,33,36,39,43,48,50,51 , and 5 studies reached statistical significance 33,43,48,50,51 . Overall, based on the secondary cases, 6.9% (95% CI: 5.7%, 8.2%) of cases were hospitalized.…”
Section: Resultsmentioning
confidence: 99%
“…Among 31 studies reporting symptom status of cases (Fig. 4), 26 studies reported higher proportion of being symptomatic for index cases than secondary cases 15,16,19,[21][22][23][24][25][26][28][29][30]32,[34][35][36][38][39][40][41][42]44,46,47,49,51 , and 15 studies reached statistical significance 15,19,22,[24][25][26][28][29][30]32,36,[38][39][40]49 . Overall, based on the secondary cases, 90.8% (95% CI: 90.3%, 91.3%) of cases were symptomatic.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Ustundag, et al, illustrated that hospitalization rates were higher in patients without household contact, which is different from Jannuzzi et al, findings. One of the reasons for the heterogeneity is that asymptomatic patients with a low-risk contact might not have been tested; some COVID-19 patients "without household contact" were also untested, and the actual number of the patients "without household contact" remained unknown [3]. CoV-2, and rates were lower during the school period when interactions with other children were expected to increase disease transmission [5].…”
mentioning
confidence: 99%
“…findings. One of the reasons for the heterogeneity is that asymptomatic patients with a low-risk contact might not have been tested; some COVID-19 patients ‘without household contact’ were also untested, and the actual number of the patients ‘without household contact’ remained unknown [ 3 ].…”
mentioning
confidence: 99%